Effect of Vitamin D Supplementation and Calcium in Reducing the Risk of Preeclampsia: Meta-Analysis - Fajriyani, Fanny Kartika; Pamungkasari, Eti Poncorini; Murti, Bhisma (Masters Program in Public Health, Sebelas Maret University, 2020)
Background: Preeclampsia (PE) is a major complication in pregnancy and a major cause of maternal and fetal morbidity and mortality. Analysis of risk factors and prevention of preeclampsia are needed to reduce the adverse effects of preeclampsia. Important supplements during pregnancy to prevent the increase in blood pressure of pregnant women are Vitamin D and calcium. This study aimed to analyze the effect of vitamin D and calcium supplementation on reducing the risk of preeclampsia.Subjects and Method: This study is a meta-analysis of a number of randomized controlled trials. The articles used in this study were obtained from several databases including PubMed, Google Scholar, Springerlink, and Sciencedirect. The articles used in this study were those published from 2002-2020. The article search was carried out by considering the eligibility criteria defined using the PICO model. P: Pregnant women, I: vitamin D and calcium, C: placebo, and O: preeclampsia. The keywords to find articles are as follows: